Inégalités environnementales et hétérogénéité des préférences pour les solutions fondées sur la nature - Cécile Hérivaux; Philippe Le Coent (Développement Durable et Territoires)
This article analyses the influence of environmental inequalities on people’s preferences for Nature-based Solutions aiming at reducing flooding risks. The approach is based on the spatial analysis of three forms of environmental inequalities (access, exposure and distributional inequalities), and their influence on the preference profiles of 399 residents of the Lez catchment. The results show that preferences are spatially heterogeneous and influenced by these inequalities observed along an urban-rural gradient. We recommend analysing these environmental inequalities when designing Nature-based Solutions to improve their consideration in public policies.